Dukungan Keluarga terhadap Kepatuhan Minum Obat pada Pasien DM Tipe II - Reny Sulistyowati; Agnes Dewi Astuti (Jurnal Surya Medika (JSM), 2020)
The level of adherence usually decreases in patients with chronic conditions compared to acute conditions; this is related to the long-term nature of chronic disease due to the most rapid decrease in adherence after the first 6 months of therapy. The decline in compliance not only resulted in poor health outcomes but also had a significant impact on health costs. The purpose of this study was to determine family support for medication adherence in type 2 DM patients. This study used descriptive correlational using a cross-sectional study approach of 100 respondents. Patient demographic data and family support were obtained using a questionnaire while the level of compliance used Morisky Medication Adherence Scales. The results show that there is a relationship between family support and medication adherence in patients with type 2 diabetes, which is viewed from 4 dimensions: appreciation support, emotional support, information support, and instrumental support. Support from family can improve medication adherence in type 2 DM patients.